THE ROLE OF DIGITAL TECHNOLOGIES IN THE ECONOMIC DEVELOPMENT OF CLUSTERS IN AGRICULTURE - Gulyamov Saidasror Saidakhmedovich; Mardanov Khusniddin Kholbazarovich; Gulyamov Saidakhror Saidakhmedovich; Dadabayev Qobil Kasimboyevich; Rasulova Muxabbat Tishabayevna (Scholar Express Journals, 2024)
The article examines the effectiveness of investments in innovative activities in agriculture and ways to evaluate it and increase the economic efficiency of its use.
Keywords: relevance of innovative technologies; implemented investments; technological innovations